Thermography to assess grapevine status and traits opportunities and limitations in crop monitoring and phenotyping – a review - La Fata, Antonio (2022)
Mestrado em Engenharia de Viticultura e Enologia (Double degree) / Instituto Superior de Agronomia. Universidade de Lisboa / Faculdade de Ciências. Universidade do Porto